Measuring and accounting for community capabilities in Kordofan, Sudan - El-Harizi, Khalid; Klemick, Heather (International Food Policy Research Institute, 2007)
Parallel to the growing attention being devoted to the relationship between empowerment and development, an increasing number of tools are being developed to measure empowerment and determine the link between these two phenomena. This paper details the methodological processes used to construct, test and possibly refine one such instrument, the Community Capability Index, an innovative tool to measure community capabilities in the domain of natural resource governance. Empirical reference is made to research conducted in 85 villages in North and South Kordofan, Sudan. Following this, the paper presents findings from analyses of the determinants of community capabilities, including geographic, economic, and institutional variables. The results suggest that in Kordofan a number of factors influence capabilities. Possessing a village market, proximity to the nearest town, and access to credit are economic variables that have a significant and highly positive effect on community capabilities. Regarding the environment, capabilities are found to be greater where there is more rainfall, but access to groundwater from lower-quality aquifers and cracking clay soils have negative impacts on capabilities. War shocks, as might be expected, have a negative and significant effect. Particularly interesting is the generally weak correlation found between capabilities and wealth, along with strong correlations between institutional and social dimensions of community capabilities and participation in donor-funded projects. This combination suggests that development interventions must take into account the non-identity of poverty reduction and empowerment processes, at least when the targeted agents are communities rather than individuals or households. The findings reveal areas for further investigation into the relationship between the determinants and dimensions of capabilities, and the potential significance of the relationship for some dimensions suggests context-specific interventions to strengthen the relevant capabilities.